Immunotherapy for Ovarian Cancer: What's Next? - Kandalaft, Lana E. (American Society of Clinical Oncology, 2011)
In the past decade, we have witnessed important gains in the treatment of ovarian cancer; however, additional advances are required to reduce mortality. With compelling evidence that ovarian cancers are immunogenic tumors, immunotherapy should be further pursued and optimized. The dramatic advances in laboratory and clinical procedures in cellular immunotherapy, along with the development of powerful immunomodulatory antibodies, create new opportunities in ovarian cancer therapeutics. Herein, we review current progress and future prospects in vaccine and adoptive T-cell therapy development as well as immunomodulatory therapy tools available for immediate clinical testing.